Radiation safety protection knowledge and practice among hospital health workers working in radiation-emitting environments - Magadzire, Fletcher (BUSE, 2025)
Radiation safety is a serious global concern, with low-and middle-income countries, including Zimbabwe, facing challenges in safeguarding adequate protection for hospital workers in radiation-emitting environments. Notwithstanding legal frameworks like Radiation Protection Act (Chapter 15:15) and SI 62 of 2011, compliance remains inconsistent due to knowledge gaps, infrastructural limitations and weak institutional support Objective: This study aimed to assess radiation safety knowledge and practice levels among Zimbabwean hospital workers, identify compliance barriers, and develop an evidence-based framework for improving occupational radiation safety. Methods and materials: A mixed methods sequential explanatory design was used. Quantitative data were collected through a structured questionnaire (n = 70), while qualitative insights were gathered utilizing key informant interviews (n = 7) and an observation checklist. Descriptive statistics and correlation analysis were conducted using SPSS.A thematic analysis was used on qualitative data. A critical review of existing frameworks guided the development of a new model-Integrated radiation safety knowledge and practice model (IRS-KPM). Key findings: The average knowledge score was 66.8% and practice score was 63.4%, both indicating moderate levels. Training and education were significantly associated with higher scores. Compliance gaps were observed in use of personal protective equipment and safety briefings. Thematic analysis identified barriers such as equipment shortages, inadequate staffing, leadership gaps, and weak policy enforcement. Experts validated the IRS-KPM model as feasible, relevant and comprehensive. Conclusions: Findings show a disconnect between knowledge and practice, indicating the need for structured training and leadership-driven safety culture. The IRS-KPM model offers a contextualized framework to augment radiation safety compliance. The study’s insights are generalizable to similar low-resource healthcare settings. Further research is recommended to pilot the framework across diverse institutions.